Ethics, public health and technology responses to COVID‐19 - Miller, Seumas (Bioethics, 2021)
The COVID‐19 pandemic has infected millions around the world. Governments initially responded by requiring businesses to close and citizens to self‐isolate, as well as funding vaccine research and implementing a range of technologies to monitor and limit the spread of the disease. This article considers the use of smartphone metadata and Bluetooth applications for public health surveillance purposes in relation to COVID‐19. It undertakes ethical analysis of these measures, particularly in relation to collective moral responsibility, considering whether citizens ought, or should be compelled, to comply with government measures.